Credibility and Transparency of Central Banks: New Results Based on Ifo's World Economicy Survey - Sandra Waller; Jakob de Haan (Center for Economic Studies and ifo Institute (CESifo), 2004)
This paper reports the results of a survey among private sector economists about credibility and transparency of central banks. In line with the survey of Alan Blinder among central bankers, we asked participants in Ifo's World Economic Survey to answer questions on the importance and determinants of credibility. The results of both surveys are very comparable. Credibility is considered to be important to attain price stability at low cost, while the best ways to earn credibility are a history of honesty and a high level of central bank independence. According to our respondents, the Federal Reserve is the most credible, transparent and independent central bank out of seven large central banks. The ECB is not perceived as highly credible or tranparent, even though our respondents consider it to be very independent.
Keywords: 330; transparency; credibility; independence; monetary policy; ECB